PHARMACOECONOMICAL ASPECTS OF SELF-MEDICATION; A COMMUNITY PHARMACY SURVEY IN NORTHERN KERALA - PUTHIYEDAM, NAINA LIZ; SAJAN, ANJANA; T, ARUNA; VS, VINEETH; SS, KIRON; SUNNY, SMRITHY (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The main objectives of the study are to identify the socio-economic characteristics of lay persons who engage in self-medication activities, to determine the economic aspects of self-medication, to conduct cost minimization analysis, and to determine the consequences of self-medication. Methods: A cross-sectional survey was conducted in community pharmacies throughout Northern Kerala for a period of 6 months from April 2021 to September 2021. A total of 300 participants were selected through consecutive sampling. Results: 117 people were from upper middle class families based on Kuppuswamy’s scale. A majority of participants considered self-medication for economic benefits which confirmed that self-medication is closely related to the financial background of the respondents. The costs saved were measured by calculating the costs associated with hospital visits by them or family in the past 6 months for similar manifestations. During the study, the cost of branded drugs prescribed was determined as 70–1498.78% more than the generic versions. Hence, patients are spending much more on their treatment unaware about other alternative options. 117 participants experienced an adverse drug reaction after taking the medication, and 134 participants responded that their symptoms were not improving and 99 entrants had to visit the hospital who had an economic burden due to delay in detection of the disease. Conclusion: Thus, the study concluded that there is a strong relationship between pharmacoeconomics and self-medication behavior.